The Competitiveness of Hungarian Micro-Enterprises in the Pasta Market - Fehér, Ilona (Táplálkozásmarketing, 2019)
By analysing the long-term competitiveness of Hungarian dry pasta making micro and small businesses, I intend to explore its strategic potential. The changes in the competitiveness of the dry pasta sector in Hungary between 1969 and 2019 were analysed with the help of contemporary periodicals from the database of the Hungarian Agricultural Museum and Library. The changes in the competitiveness of the Hungarian dry pasta market over the period 1969-2019 were analyzed according to the six aspects of diamond model: factor conditions, demand conditions, corporate strategy, structure and rivalry, relating and supporting industries, government regulations, change. Looking at future trends in the dry pasta market, the bidirectional impact on the competitiveness of the pasta market will be affected. One effect is to move towards horizontal networking as a result of globalization, making the pasta company that is able to negotiate better in the food supply chain more competitive. The other effect is the trend of local patriotism, which stimulates the development of micro-regions and originates in the initiative of the locals: innovation of flavours, innovation in raw materials, possibilities of Hungarian ethnocentrism. In addition, retail brands are expected to grow further. As retail chains do not pass on any gains from the increase of their export volume to the processors, the manufacturers’ own brand is weakened. The study provides a long-term overview of the changes in the competitiveness of companies operating in the dry pasta market. There has been a tremendous change over the last eighty years with the innovative transformation of the pasta industry. At that time, almost all pasta products were made at home, and today the pasta group is competing for housewives by employing industrial designers.JEL Codes: M31, M39